Caffeine content of pre‐workout supplements commonly used by Australian consumers. Issue 3 (3rd October 2018) - Desbrow, Ben; Hall, Susan; O'Connor, Helen; Slater, Gary; Barnes, Katelyn; Grant, Gary
Abstract: The stimulant properties of caffeine are often promoted in pre‐workout supplements (PWS) to assist with training, reduce the perception of fatigue, and for some brands, assist body fat loss. While manufacturers of PWS often indicate the inclusion of significant amounts of caffeine, no independent verification of the caffeine content of these products exists. The aim of this investigation was to independently assess the caffeine content of popular PWS in Australia and compare these values to nutrition information panel data. Fifteen PWS were tested for their caffeine content (both within and between batches of the same product). The caffeine content of selected PWS ranged from 91 to 387 mg·serve −1 . Only 6 of the 15 PWS nutrition information panels included details on caffeine content. The percent of caffeine present ranged from 59% to 176% of packaging claims. All but one PWS contained a variation of caffeine within and between batches that was considered "practically" significant (ie, ≥40 mg·serve −1 variation). Consumers are likely to be exposed to large and variable caffeine doses if ingesting PWS. Product information panels do little to improve consumer awareness of likely caffeine intakes. Abstract : An assessment of the caffeine content of popular pre‐workout supplements sold in Australia and comparison to their nutrition information panels.